Development of the French language curriculum for special purposes (Français Sur Objective Spécifique/ FOS) in the field of tourism through a Functional Approach - Lina Syawalina (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
The research entitled